Toward Open Repository of Performance Portability of Applications, Benchmarks and Models - Marowka, Ami (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2023)
The adoption of heterogeneous computing systems based on diverse architectures to achieve exascale computing power has worsened the performance portability problem of scientific applications that were designed to run on these platforms. To cope with the challenges posed by supercomputing, new performance portability frameworks have been developed along-side advanced methods and metrics to evaluate the performance portability of heterogeneous applications. However, many studies have shown that the new methods and metrics do not produce coherent results which yield clear conclusions that are required for designing the hardware and software architectures of tomorrow's supercomputing systems. We outline a proposal to establish an open repository of performance portability of applications, benchmarks and models which will be standardized, objective, and based on strict operating and reporting guidelines. Such guidelines will ensure a fair, comparable and meaningful measure of the performance portability while the requirement for a detailed disclosure of the obtained results and the configuration settings will ensure the reproducibility of the reported results.